Establishment & Assessment of the Macroscopic Fundamental Diagrams for the City of Durban Freeway Network Using Empirical Data - Mthembu, Siphesihle Henry (Department of Civil Engineering, 2022)
The history of traffic flow studies dates to the years between the 1960s and 1970s. This paper reviews the history of traffic flow studies in the context of Macroscopic Fundamental Diagrams (MFD) to date. The recent findings have shown that understanding the Macroscopic Fundamental Diagrams (MFD) in cities can bring success in managing congestions. This study aimed to establish the Macroscopic Fundamental Diagrams (MFD) for the City of Durban Freeway network. Motivated the study was a failure seen in various transportation systems after the 2010 FIFA world cup in South African cities. This failure was associated with the adoption of the transportation system from first-world countries. The South African cities are not densified when compared to the first world countries' cities, of course, due to spatial urban planning and segregation of the past. The key lesson was that SA transportation systems problems are unique; solutions should be attributed to the existing travel demand conditions. This birthed the idea that the performance of a traffic system should uniquely serve the specific travel demands. The core aim of this study was to establish the MFD for the freeway network in the City of Durban, South Africa. Two major freeway corridors were evaluated, i,e. the National route 2 and 3. The study used loop detector data extracted from a total of 88 loop detector stations. The loop detector stations were dispersed 100-500 m apart over the network. The data was recorded in September 2019. The collected data was analysed in five minutes intervals. When the MFD was established on the network, aggregated detector loops produced a well defined MFD on the 2 nd,3rd ,16th, and the 23rd of September, whereas, on a separate day (30th of September), a scattered MFD forming a hysteresis loop was observed. The formation of the hysteresis was associated with the lack of alternative routes for drivers to avoid congestions in the network. These observations are discussed later in this paper. The study was a success as it did reveal that the MFD was an attribute of the City of Durban freeway network. The established MFD showed that the freeway network operates between the unsaturated and saturated state. This MFD does not reach the saturated flow. The highest recorded density was found at 10.11 veh/km while the highest recorded flow was found at 733.28 veh/hr. The network operates at an average speed of vav= 79.84 km/hr. The estimated average density for the network to reach the gridlocked state was calculated to be 75veh/km.